The effect of Georgia's HOPE scholarship on college major: A focus on STEM - David L. Sjoquist; John V. Winters (IZA Journal of Labor Economics, 2015)
There is growing concern that the U.S. is producing too few college graduates in science, technology, engineering, and mathematics (STEM) fields, and there is a desire to understand how various policies affect college major decisions. This paper uses student administrative records from the University System of Georgia to examine whether and how Georgia's HOPE Scholarship has affected students' college major decisions, with a focus on STEM. We find that HOPE reduced the likelihood of earning a STEM degree. The research is complementary to a forthcoming paper by the authors, but using USG administrative records allows us to address several additional issues beyond the effect of merit aid on the likelihood of earning a STEM degree, including: the effect on initial major, earned major, and the transition between them; the roles of student ability, student performance, and institutional choice; and other possible mechanisms through which merit aid affects STEM education.
Keywords: I23; J24; 330; Merit aid; HOPE scholarship; College major; STEM